Reasons to Use Cash Payment (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to find out the factors influencing the use of cash-payment in Yogyakarta. The object of this research is Super Indo as one of the biggest markets in Yogyakarta in which people usually used for shopping. It uses the quantitative approach through distributing the questionnaire. The data obtained on 100 samples with the specification of above 17 years old and time frequency more than once a week to purchase in the market. The data processed by using multiple linear regressions. There are four independent variables within this research namely, manageable, flexibility, transaction volume and charge for non-cash payment while the dependent variable is cash usage. As a result, the research shows that all the independent variables have influence simultaneously towards cash usage as the dependent variable, whereas in t test, only two variables affect positive significantly against cash usage, which are transaction volume and no transaction fees. Overall, this research provides important information for the central bank, that although the non-cash payment system has been developed, people-especially in Yogyakarta-still prefer using cash-payment for their daily transaction. The purposed of the methodology is general and can be applied to other region in order to find the differences of transaction payment.